Suitability of R404A Condensation Heat Transfer and Pressure Drop Correlations for Small Diameter Tube - Wang Xuedong; Liu Jianhua; Song Ji; Gao Yifeng; Zhu Lijun (Zhileng xuebao)
Many correlations have been proposed about R404A condensation heat transfer and pressure drop, but all of them apply for smooth tubes or microfin tubes with big diameter. Some correlations are based on 5 mm diameter tube, but the refrigerant is not R404A. Up to now, there is no correlation for R404A condensation heat transfer and pressure drop with 5 mm diameter tube. In this paper, a number of correlations were selected by variable-controlling and giving priority to refrigerant with similar properties, combining experimental test and theoretical calculation, deviation between the calculated and experimentally measured values have been compared through a large amount of data to demonstrate the applicability and revisability of the correlations. The research results indicate that modified Dobson and Chato condensation heat transfer correlation (multiplied by the correction factor 2.13) shows good predictability of condensation heat transfer coefficient of R404A in small diameter microfin tube within a deviation of ﹣14.13% to +15.51%. The friction pressure drop correlation proposed by Huang Xiangchao can well predict the friction pressure drop of R404A in small diameter microfin tube within a deviation of ﹣13.58% to +12.56%. Both correlations can provide more accurate theoretical guidance for the calculation and design of heat exchanger.